Nested Communities of Practice (CoP) Co-learning and sharing lessons learned to scale farmer centered restoration options in East Africa and the Sahel - Winowiecki, Leigh Ann; Sinclair, Fergus L. (World Agroforestry Centre, 2020)
Drawing insight from work in Mali, Ethiopia, Kenya and Niger to scale land restoration across the drylands in Africa, the brief defines and describes the Nested Communities of Practice (CoPs) approach and how this project implemented these with key stakeholders (farmers, community facilitators, NGOs, government and researchers) to foster co-learning and sharing with evidence in East Africa and the Sahel. Addressing land degradation is key to achieving food and nutrition security and requires active and deliberate engagement of multiple stakeholders including farmers, NGOs, government and researchers. In order to reach the land restoration targets set by National Governments and the United Nations Sustainable Development Goals (SDGs), successful restoration efforts need to reach larger numbers of farmers and extend over larger areas than has previously been achieved. A key constraint to scaling restoration is that the ecological, economic, social, political and institutional context varies from household to household, as well as from village to village and that no one technology will suit all. This means active continual learning and communication between farmers, local community leaders, NGO partners, government, researchers and development partners is critical to ensure context relevant solutions are implemented to meet food and nutrition needs as well as restoration targets.